2016
DOI: 10.1038/ncomms13894
|View full text |Cite
|
Sign up to set email alerts
|

Targeting dendritic cells to accelerate T-cell activation overcomes a bottleneck in tuberculosis vaccine efficacy

Abstract: The development of a tuberculosis (TB) vaccine that induces sterilizing immunity to Mycobacterium tuberculosis infection has been elusive. Absence of sterilizing immunity induced by TB vaccines may be due to delayed activation of mucosal dendritic cells (DCs), and subsequent delay in antigen presentation and activation of vaccine-induced CD4+ T-cell responses. Here we show that pulmonary delivery of activated M. tuberculosis antigen-primed DCs into vaccinated mice, at the time of M. tuberculosis exposure, can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 70 publications
4
114
0
Order By: Relevance
“…Recent extensive studies into the immunophysiology of TB associated granulomas have shed new light on what could be considered a protective response. 75 Vaccine development may also be advancing through the use of viral vectors; one promising approach that is still in preclinical stages of evaluation uses a Rhesus cytomegalovirus vector expressing multiple TB antigens (RhCMV/TB). By this approach, either complete protection against TB challenge and disease in some Rhesus macaques or partial protection was observed after immunization.…”
Section: Vaccines In Early Stages Of Development With Potential To Rementioning
confidence: 99%
“…Recent extensive studies into the immunophysiology of TB associated granulomas have shed new light on what could be considered a protective response. 75 Vaccine development may also be advancing through the use of viral vectors; one promising approach that is still in preclinical stages of evaluation uses a Rhesus cytomegalovirus vector expressing multiple TB antigens (RhCMV/TB). By this approach, either complete protection against TB challenge and disease in some Rhesus macaques or partial protection was observed after immunization.…”
Section: Vaccines In Early Stages Of Development With Potential To Rementioning
confidence: 99%
“…Our mechanistic studies demonstrated that IL-17 induced chemokines localize cytokine-producing T-cells near Mtb -infected macrophages, forming lymphoid follicles within granulomas to mediate Mtb control [11, 18]. In combination with DC transfer, a HLT-TB mucosal vaccine can provide superior near-sterilizing vaccine-induced protection against Mtb infection [8, 17, 19]. Despite the ability of these experimental mucosal adjuvants to induce protective Th17 responses and confer vaccine-induced protection, there are serious concerns regarding the safety of toxin subunits as mucosal adjuvants in human vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, while persistent TNFRp55 expression leads to potential defective T cell responses during chronic M. tuberculosis infection (61), sustained TNF-α expression by DCs enhances maturation and generates a much more robust T cell response (62). Thus, DCs are positioned to serve as an important link between innate and adaptive immunity and may act as useful targets for immunotherapy and vaccine development (63,64). …”
Section: Antigen Presentationmentioning
confidence: 99%